Physico-mechanical properties changes in virgin and recycled polyethylene fibers during recycling process - Jozefita Marku; Elias Chatzhitheodoridis (Zaštita Materijala)
The aim of this work is to study the changes of physico-mechanical properties of polyethylene during recycling stages. All raw materials were taken virgin and recycled polyethylene granules used for producing plastic bags. Initially they were identified with the vibration spectroscopy FT-IR and Raman, which marked the presence of additives in recycled samples. As recycling process was used as a micro-pilot system; comprising the melt flow index device and a universal mill grinding. Among mechanical properties that were identified were density, specific gravity, melt flow index, yield strength and elasticity modulus and tensile strength. From the results analysis were observed changes in physical and mechanical properties for polyethylene samples by recycling cycles.